2005
DOI: 10.2337/diabetes.54.9.2674
|View full text |Cite
|
Sign up to set email alerts
|

Overactivation of S6 Kinase 1 as a Cause of Human Insulin Resistance During Increased Amino Acid Availability

Abstract: To examine the molecular mechanisms by which plasma amino acid elevation impairs insulin action, we studied seven healthy men twice in random order during infusion of an amino acid mixture or saline (total plasma amino acid ϳ6 vs. ϳ2 mmol/l). Somatostatin-insulinglucose clamps created conditions of low peripheral hyperinsulinemia (ϳ100 pmol/l, 0 -180 min) and prandial-like peripheral hyperinsulinemia (ϳ430 pmol/l, 180 -360 min). At low peripheral hyperinsulinemia, endogenous glucose production (EGP) did not ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
288
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(312 citation statements)
references
References 46 publications
16
288
8
Order By: Relevance
“…In contrast to wild-type littermates, transgenic mice lacking S6K1 kinase (S6K1-deficient mice) displayed a strong resistance to age-and diet-induced obesity and insulin resistance (37). Moreover, because wild-type mice on a high-fat diet demonstrated significantly elevated S6K1 kinase activity and serine phosphorylation of IRS-1, it has been suggested that under conditions of nutrient saturation, S6K1 kinase may negatively regulate insulin signaling and sensitivity (37,53,54). Because insulin resistance can be induced by mechanisms other than nutritional excess, serine phosphorylation of IRS-1 has been examined under various circumstances.…”
Section: Serine Phosphorylation Of Irs-1mentioning
confidence: 99%
“…In contrast to wild-type littermates, transgenic mice lacking S6K1 kinase (S6K1-deficient mice) displayed a strong resistance to age-and diet-induced obesity and insulin resistance (37). Moreover, because wild-type mice on a high-fat diet demonstrated significantly elevated S6K1 kinase activity and serine phosphorylation of IRS-1, it has been suggested that under conditions of nutrient saturation, S6K1 kinase may negatively regulate insulin signaling and sensitivity (37,53,54). Because insulin resistance can be induced by mechanisms other than nutritional excess, serine phosphorylation of IRS-1 has been examined under various circumstances.…”
Section: Serine Phosphorylation Of Irs-1mentioning
confidence: 99%
“…Caution is, however, warranted given reports that high physiologic levels of amino acids can induce insulin resistance in humans [56,57]. Specifically, Tremblay et al [57] have reported that increased availability of amino acids impairs the ability of insulin to attenuate glucose production and the ability of muscle to dispose of excess glucose.…”
Section: Amino Acids and Muscle Metabolism In Chronic Diseasementioning
confidence: 99%
“…Specifically, Tremblay et al [57] have reported that increased availability of amino acids impairs the ability of insulin to attenuate glucose production and the ability of muscle to dispose of excess glucose. Their data suggest that the mechanisms underlying amino acid-induced insulin resistance include overactivation of mammalian target of rapamycin and 70-kDa ribosomal protein S6 kinase, along with the inhibition of insulin receptor substrate-1 via serine phosphorylation.…”
Section: Amino Acids and Muscle Metabolism In Chronic Diseasementioning
confidence: 99%
“…Studies of regulation of these and other pathways during oral feeding in humans are demanding because of non-steady-state circulating hormones and substrates and require extremely complex experimental protocols. Addi-tionally, since nonphysiological hyperaminoacidemia has been shown to restrain insulin-mediated glucose uptake in euglycemic clamps (27,47), quantifying this response in fed steadystate conditions should permit elucidation of whether this observation has physiological/pathophysiological implications.…”
mentioning
confidence: 99%